Intervenção piloto em idosos independentes submetidos às práticas educativas em saúde - Antoniassi, Arlete (2016)
An aging population is a disturbing worldwide phenomenon which has implications both for society and for the elderly people. Cognitive impairment associated or not to chronic degenerative diseases limits the life ratio of the elderly. Depression, the most common psychiatric syndrome among elderly, impairs their quality of life and can cause or increase functional disabilities. Thus, this study characterized independent elderly, users of the Family Health Unit from Vila Sabiá, in Sorocaba (SP) and described the experience of a pilot intervention of educational practices in health of an elderly group. This is a descriptive and quantitative study approved by the Research Ethics Committee, developed with 35 independent elderly. Seven individuals participated in a pilot intervention with educational practices in health, for 12 weeks, from August to October in 2014. The educational health practices involved bodily movements, several thematic content, artistic and recreational activities. Statistical data were obtained through 5 instruments: a questionnaire on socioeconomic, demographic and health-related aspects; the Mini-Mental State Examination (MMSE) for cognitive assessment; the reduced Geriatric Depression Scale (GDS-15) for screening of depressive mood disorder; Functional Activities Questionnaire by Pfeiffer (FAQ) for evaluation of Daily Life Instrumental Activities; the WHOQOL-Bref for the quality of life. We used the chi-square test on the correlation of data and the Student "t" test in comparing the results before and after the educational practices in health intervention pilot group. Results: The majority of subjects were female, aged 60-65 years old, Caucasians workers and residents at proper home with spouse, Catholics and with elementary school level. There was prevalence of hypertension, type 2 diabetes, obesity and depressive symptoms. The type of joint housing of individuals contributed to the diagnosis of hypertension (p=0,03). The faith/ personal belief/ spirituality were individual protective factors of diabetes (p=0,03). The group participating in the intervention pilot showed statistically significant change in the total score of the MMSE (p=0,03). Conclusions: factors related to the appearance and maintenance of the major NCDs (hypertension, diabetes and obesity) and depressive symptoms can be prevented through behavioral changes and reorganization in lifestyle. Educational practices in health contributed to the improvement in the cognitive profile of the elderly subjects during the studied period